POTENSI ENERGI TEORITIS DAN TEKNIS DARI LIMBAH PERTANIAN DI KABUPATEN KUANTAN SINGINGI - Yelmira Zalfiatri (Jurnal Ilmu Lingkungan, 2016)
Kuantan Singingi an area that has abundant natural wealth as a potential energy source. Source of energy comes from non-renewable energy and renewable energy. But it is unfortunate especially energy potential of renewable energy is not recorded properly in terms of quality and quantity.The aims of study toprovide information about the potential alternative energy including type, distribution and quantity ofenergy sources. Dataacquisition and distribution of potentialin the form ofsecondary dataobtained from therelevant institution. Institution involved inthe study consistedofRegional Planning Agency, Department of Agriculture and Foodstuffs, the Agriculture Agency, Department of Animal Husbandry and Sanitation Department. Secondary datawere processed using themethod of Biomass Energy Europe (BEE) in order to obtain primary datain theoretical energy pontential and technical energy potential. Total the oretical energy potential of biomass in Kuantan Singingi is 4.226.308,23GJ/year consistof primere and skunder agricultural residues are 3.759.430,79 GJ/year (89%) and animal waste 466.877,44 GJ/year (11%). The total technical energy potentialis 1.514.203,99GJ/yearconsist of primere and skunder agricultural residues1.327.453,01 GJ/ year (87,7%) and animal waste186.750,98 GJ/ year (12,3%).